2015
DOI: 10.1111/pbr.12292
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation and differential expression of VRN‐A1 in durum wheat genotypes varying in the vernalization response

Abstract: The purpose of this research was to study the effect of vernalization on flowering time in thirty accessions of Triticum turgidum spp. durum. To this end, screening of allelic variation at VRN‐1 loci was carried out using PCR‐based markers and DNA sequencing, and gene expression analysis was performed in two and four developmental stages, with and without cold treatment. In non‐vernalized plants, average days to flowering ranged from 34 to 99 days and only one accession was observed to remain at the vegetative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…The winter allele vrn-A1 was only identified in two landraces, but it was not present in the present set of modern cultivars. This result is in agreement with the clear preponderance of spring dominant alleles at the Vrn-A1 gene found previously in improved durum wheat varieties from Argentina, CIMMYT, France, Italy, and Hungary (Basualdo et al, 2015). The allele Vrn-A1a, found previously in durum wheat varieties from Russia (Muterko et al, 2016b) was not present in the germplasm analyzed here.…”
Section: Vrn-1 and Ppd-1 Allele Frequency And Geographic Distributionsupporting
confidence: 93%
“…The winter allele vrn-A1 was only identified in two landraces, but it was not present in the present set of modern cultivars. This result is in agreement with the clear preponderance of spring dominant alleles at the Vrn-A1 gene found previously in improved durum wheat varieties from Argentina, CIMMYT, France, Italy, and Hungary (Basualdo et al, 2015). The allele Vrn-A1a, found previously in durum wheat varieties from Russia (Muterko et al, 2016b) was not present in the germplasm analyzed here.…”
Section: Vrn-1 and Ppd-1 Allele Frequency And Geographic Distributionsupporting
confidence: 93%
“…The evolution of spring-habit cultivars from winter-habit accessions played a key role in the postdomestication spread of wheat. However, studies on the major vernalization gene VRN1 have been mostly limited to hexaploid wheat species and very few reports from tetraploid species can be found in the literature [48,49]. None of the durum wheat accessions characterized here showed the Vrn-A1a allele described in spring-habit hexaploid wheat varieties, which is in accordance with what has been found in other studies [50,51].…”
Section: Durum Wheat Landracessupporting
confidence: 90%
“…Vernalization genes are the main determinants of the growth habit (i.e., winter or spring) in temperate cereals, and by affecting the vegetative to reproductive transition, these genes are involved in the ability of wheat plants to adapt to a wide range of environments [48]. The evolution of spring-habit cultivars from winter-habit accessions played a key role in the postdomestication spread of wheat.…”
Section: Durum Wheat Landracesmentioning
confidence: 99%
“…This is in line with what can be expected since accessions carrying the recessive Vrn allele would not be able to flower under those conditions. Previous studies suggested Vrn-1 to be essential in the control of winter flowering types of common wheat [35][36][37], and durum wheat [22,27,[38][39][40][41][42]. However, results of the present research show only partial agreement with the literature, with a clear role of Vrn1 confirmed only when no cold temperatures occur (see PhEnv3 and 4 in Table 1), but substantially no effect in PhEnv where weak or strong vernalization requirements can be met (see PhEnv1 and 2 in Table 1).…”
Section: Known Loci Involved In the Control Of Flowering Time In Durusupporting
confidence: 55%